Porosity and morphology control of mesoporous Cu-BTC Metal-Organic Framework microparticles - Kobra Vazirinezhad; Fatemeh Shariatmadar Tehrani; Sedigheh Zeinali (Progress in Physics of Applied Materials)
In this study, Cu-BTC structures, one of the most widely used metal-organic frameworks (MOF), were synthesized by solvothermal technique, and the effect of metal-to-ligand ratio and the solvent content on their crystalline structure, chemical bonding, morphology, and porosity properties was investigated systematically by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy, and N2 adsorption-desorption measurements, respectively. The results demonstrate that the metal-to-ligand molar ratio although does not noticeably affect the crystalline nature of the product, but observably controls the morphology so that spherical to octahedral microparticles can be achieved. In addition, the specific surface area (SSA) and total pore volume of the mesoporous structures are significantly enhanced to 969.5 m2g-1 and 0.41 cm3g-1, respectively, for a 1:1 molar ratio of metal to ligand. On the other hand, changing the solvent content greatly increased the SSA (1364.8 m2g-1) and total pore volume (0.561 cm3g-1) by ~41% and ~37%, respectively. This would be promising finding for wide range of applications requiring high SSA materials.